Single Mothers in Russia : Household Strategies for Coping with Poverty - Lokshin, Michael; Harris, Kathleen Mullan; Popkin, Barry (World Bank, Washington, DC, 2015)
The authors describe trends in single parenthood in Russia, examining factors that affect living arrangements in single-mother families. Before economic reform, single mothers and their children were somewhat protected form poverty by government assistance (income support, subsidized child care, and full employment guarantees). Economic reform in Russia has reduced government transfers, eliminated publicly subsidized pre-school care programs, and worsened women's opportunities in the labor market. The loss of government support has eroded family stability, and left single mothers at increased risk of poverty. Over the last decade, the proportion of households headed by women has increased rapidly, raising the risk of poverty. Single-parent families now represent nearly a quarter of all Russian households. Using seven rounds of data from the Russian Longitudinal Monitoring Survey, the authors investigate how household living arrangements, and other factors, affect income in single-mother families. They find that a single parent with more earning power, and child benefits is more likely not to live with relatives. But single mothers are increasingly choosing to live with other adults, or relatives, to survive, and to raise their children in times of economic stress, and uncertainty. Half of all single mothers in Russia live with their parents, their adult siblings, or other adult relatives. Help from relatives is important to single-mother families, and that help - including the sharing of domestic and childcare duties - is more efficient, and productive when the single parent lives with the family. The other half live in independent residences, and face increased risk of poverty.